#### Answer

$$ R_{uvw}= 2(v+w)^{-3}=\frac{2}{(v+w)^{3}}.$$

#### Work Step by Step

Since $ R(u,v,w)=\frac{u}{v+w}$, then we have
$$ R_{u}=\frac{1}{v+w}=(v+w)^{-1},$$
$$ R_{uv}= -(v+w)^{-2},$$
$$ R_{uvw}= 2(v+w)^{-3}=\frac{2}{(v+w)^{3}}.$$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ R_{uvw}= 2(v+w)^{-3}=\frac{2}{(v+w)^{3}}.$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.